Devil's breath : a Max Tudor mystery - Malliet, G. M., 1951- (Malliet, G. M., 1951- Max Tudor novel, 2017)
"Agatha Award-winning author G.M. Malliet has charmed mystery lovers, cozy fans, and Agatha Christie devotees with her critically acclaimed mysteries featuring handsome spy-turned-cleric Max Tudor. In The Haunted Season, Max's former life as an MI5 agent caught up with him, threatening his newfound happiness with Awena and baby son Owen. Realizing there is no escape from his past, Max, with his bishop's tacit permission, has offered his services to MI5 on an as-needed basis. And in Devil's Breath, it's time for Max to follow through. The body of glamorous film star Margot Browne has washed ashore from a luxury yacht and Max's former colleague Patrice Logan wants his help to find the murderer. It's a perfect "closed circle" murder since victim Margot must have been killed by one of the actors, stylists, screenwriters, or second-tier royalty aboard. Patrice suspects the yacht's owner, a playboy film director she's been keeping tabs on for smuggling, but Max isn't so sure. Max and DCI Cotton interview the suspects as they loll about one of the luxury hotels dotting the waterfront. The investigation into Margot's lurid past uncovers a host of motives--it seems she was not the only person on board with a secret they'd kill to keep"--